Fatores intervenientes na segurança do trabalho de abatimentomecanizado de rochas instáveis em uma mina subterrânea de ouro - Mario Parreiras de Faria (2008)
Mortality rates due to work-related accidents are high in the mining industry. Operators identify unstable or loose rocks before starting work, to increase mine safety. These operators work under high risk conditions. The introduction of a scaler device has aimed at controlling exposure to risk during scaling of loose rock activities. The purpose of this study was to identify intervening factors related to safety at work in an underground mine. A qualitative approach was used, combining document analysis and interviews of six workers done in four collective sessions. These individuals work in an underground mine that extracted 19.6% of the Brazilian gold production in 2005. The company operates an 800-meter deep mine; it employs 840 workers. Introduction of the scaler yielded safety benefits and minimized the required physical effort for scaling loose rocks. It did not, however, eliminate the risk of accidents and exposure to harmful environmental factors. Organizational issues and equipment-related concepts worsened the situation by not taking into account the physical and psychological aspects of operators, as well as their implied management of this activity. Closeness to the work itself and validation of worker memory and knowledge about accident risk management may be beneficial for prevention policies.